Similar cardioventilatory but greater neuromuscular stimuli with interval drop jump than with interval running - Ducrocq, G. P.; Hureau, T. J.; Meste, O.; Blain, G. M. (International Journal of Sports Physiology and Performance, 2019)
Context: Drop jumps and high-intensity interval running are relevant training methods to improve explosiveness and endurance performance, respectively. Combined training effects might, however, be achieved by performing interval drop jumping. Purpose: To determine the acute effects of interval drop jumping on oxygen uptake (VO2)—index of cardioventilatory/oxidative stimulation level and peripheral fatigue—a limiting factor of explosiveness. Methods: Thirteen participants performed three 11-minute interval training sessions during which they ran 15 seconds at 120% of the velocity that elicited maximal VO2 (VO2max) (ITrun), or drop jumped at 7 (ITDJ7) or 9 (ITDJ9) jumps per 15 seconds, interspersed with 15 seconds of passive recovery. VO2 and the time spent above 90% of VO2max (TO2max) were collected. Peripheral fatigue was quantified via preexercise to postexercise changes in evoked potentiated quadriceps twitch (DeltaQT). Power output was estimated during ITDJs using optical sensors. Results: All participants reached 90% of VO2max or higher during ITrun and ITDJ9, but only 11 did during ITDJ7. TVO2max was not different between ITrun and ITDJ9 (145 [76] vs 141 [151] s; P = .92) but was reduced during ITDJ7 (28 [26] s; P = .002). Mean DeltaQT in ITDJ9 and ITDJ7 was not different (-17% [9%] vs -14% [8%]; P = .73) and greater than in ITrun (-8% [7%]; P = .001). No alteration in power output was found during ITDJs (37 [10] W/kg). Conclusion: Interval drop jumping at a high work rate stimulated the cardioventilatory and oxidative systems to the same extent as interval running, while the exercise-induced increase in fatigue did not compromise drop jump performance. Interval drop jumping might be a relevant strategy to get concomitant improvements in endurance and explosive performance.